Proza macedońska XXI wieku. Literatura „małego narodu” w przekładach na język polski - Moroz-Grzelak, Lilla (Przekłady Literatur Słowiańskich, 2020)
This article presents 21st-century Macedonian prose as it appears in contemporary Polish translation. Novels and stories by Macedonian authors are evidence of the great degreee to which this literature has recently developed. Topics under consideration include an analysis of the fine quality of modern Macedonian prose, as well as the high attainment of its Polish translators, who, using their own translation strategies, successfully transfer one cultural code to another.